Psychosocial Correlates of Young Females Suffering from Polycystic Ovarian Syndrome (PCOS) - Rafique, Saher; Ilyas, Uzma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore the psychosocial correlates of women under treatment for polycystic ovarian syndrome (PCOS). Study Design: Cross sectional study. Place and Duration of Study: Different Clinics and Hospitals of Lahore and Gujranwala, from Aug 2019 to Nov 2020. Methodology: Single women seeking treatment for PCOS were included in the study. Derriford appearance scale and social interaction anxiety scale were used in this study. Results: A total of 180 women were included in the study. The result indicated significant positive correlation between appearance distress and social anxiety (r=0.41, p<0.001). Majority of women were visiting beauty parlors to evade facial hair and buying products to conceal their acne. Conclusion: Women diagnosed with PCOS reported to experience the appearance distress and anxiety specifically in social gatherings.